Pengolahan Buah Lindur (Bruguiera gymnorrhiza) Sebagai Pengganti Tepung Terigu Dalam Kue Semprit - I Made Purwa Dana Atmaja; Ni Nyoman Sri Melinita (JURNAL GASTRONOMI INDONESIA, 2022)
This study aims to describe the process of processing lindur fruit flour and the quality of the spritz cookies with lindur fruit flour in terms of color, aroma, taste and texture aspects. This type of research is experimental research by processing lindur fruit into flour which is then used as a substitute for flour in making syringe cakes. Data collection methods used in this research are observation, documentation, and organoleptic test methods. Organoleptic tests were carried out by 25 trained panelists to determine the quality of the syringe cake from lindur fruit flour in terms of color, aroma, taste and texture. The results of the organoleptic assessment were carried out using a Likert scale which was then analyzed descriptively qualitatively. The results of this study in the form of a description of the results of processing lindur fruit into flour and the quality of the spritz cookies from lindur fruit flour, in terms of color, it got an average score of 86.4% with very good interpretation criteria. Based on the results of the study, it can be concluded that lindur fruit can be processed into flour with the result that flour is fine but has a darker color than wheat flour and the resulting spritz cookies has very good quality in terms of color, texture, aroma and taste